Objectified Body Consciousness, Body Image Control in Photos, and Problematic Social Networking: The Role of Appearance Control Beliefs - Boursier, Valentina; Gioia, Francesca; Griffiths, Mark D. (Frontiers in Psychology, 2020)
At present, adolescents’ photo-taking and photo-sharing on social media represent ubiquitous practices and objectified body consciousness might offer a useful framework to explore online self-presentation and social networking site (SNS) use. Indeed, SNS might represent highly accessible medium for socializing with self-objectification. However, the relationship between objectified body consciousness components and problematic SNS use is still understudied. The present study evaluated the previously unexplored predictive role of appearance control beliefs on problematic SNS use, testing the mediating effect of body image control in photos. A total of 693 adolescents (55% females; mean age 16 years) participated in the study. Results showed the negatively predictive role of appearance control beliefs on control over body image in photos. Moreover, body image control in photos mediated the appearance control beliefs’ negative effect on problematic SNS use. The present study tested the unexplored effect of appearance control beliefs upon problematic SNS use, contributing to the objectified body consciousness research field and the ongoing debate concerning predictive and protective factors in problematic SNS use.